YIA 03-01 VALIDATION OF GENETIC DETERMINANTS OF UNMET NEEDS IN THE TREATMENT OF KIDNEY DISEASE IN TYPE-2 DIABETES. (September 2016) - Simon, Paul; Krajčoviechová, Aelna; Harvey, Francois; Haloui, Mousnif; Marois-Blanchet, Francois-Christophe; Chalmers, John; Woodward, Mark; Marre, Michel; Tremblay, Johanne; Hamet, Pavel
Abstract : Objective: We have previously reported the genetic determinants of unmet renal needs in Type 2 Diabetic (T2D) patients of the ADVANCE study (Abstract 0105-PD, IDF - World Diabetes Congress, Vancouver, 2015). We report here the external validation of several of these loci. An improved knowledge of the genetics linked to worsening diabetic nephropathy will offer insights on how to better manage this complication of diabetes and hypertension in T2D patients. Design and Method: We investigated 3, 500 T2D patients of Caucasian origin included in the ADVANCE trial who were all treated with current standard therapies. These patients were genotyped with Affymetrix Human Genome-Wide SNP arrays 5.0 or 6.0. Renal phenotypes were defined as increasing albuminuria (non-responders) or decreasing albuminuria (responders) and declining eGFR (non-responders) or increasing eGFR (responders) during the 5-year follow-up of ADVANCE. Genome wide association studies (GWAS) were performed using PLINK (v.1.9) for albuminuria and eGFR separately both in ADVANCE and in the Czech Post-MONICA cohort. Significant SNPs (p-value of 9x10 –5 ) were then catalogued, and a literature search was conducted to validate genes associated with these SNPs. Results: GWAS analyses showed associations with 47 genes for eGFR non-responders. Five of these, (ERC2, ZNF385D, TRAM1L1, SHANK2, and UMOD) were previously associated with GFR or kidney failure in the literature. In addition, eight of these (CACNA2D3, NOL10, ZNF385D, TENM2, CTB-7E3.1, CDH18, LMBR1 and LOC339166) are associated with GFR in Post-MONICA cohort. For albuminuria non-responders, GWAS analysis identified 57 genes. Two of these, (CERS6 and NRXN3) were previously reported in the literature as being associated with diabetic nephropathies and four of these (CERS6, STK39, DGKB and NRXN3) are associated with uric acid (which correlates with albuminuria) in Post-MONICA. Conclusions: Literature review and analysis of Post-MONICA data has enabled the validation of genes associated with renal non-response to standard therapy in the ADVANCE study.